Claire Stanziale: capstone - Stanziale, Claire, artist (Colorado State University. Libraries, 2018)
The artist's statement: With my background in fashion, earning an Associate's degree from the Fashion Institute of Design and Merchandising (Los Angeles), and my upbringing on both coasts' biggest cities, my work is infused with energy and style. In this way, my work and process lends itself to lifestyle brands - brands that sell a product but also a way of life. In thinking about design, I try to incorporate California's laidback attitude with New York's sleek style. As an artist, I value unexpected simplicity. I like to make a statement with bold color and clean design that make the viewer feel something whether that's simply joy or something deeper. I don't think graphic design should be taken so seriously. The power of fun, creative illustration is potent and I don't believe design needs to be perfect and mechanical.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design